Creatine Supplementation Improves Phosphagen Energy Pathway During Supramaximal Effort, but Does Not Improve Anaerobic Capacity or Performance - de Poli, Rodrigo de Araujo Bonetti; Roncada, Luan Henrique; Malta, Elvis de Souza; Artioli, Guilherme Giannini; Bertuzzi, Rômulo; Zagatto, Alessandro Moura (Frontiers in Physiology, 2019)
This study aimed to investigate the effects of short-duration creatine monohydrate supplementation on anaerobic capacity, anaerobic energy pathways, and time-to-exhaustion during high-intensity running. Fourteen healthy men underwent a graded exercise test followed by a "V" ̇"O" _"2max" confirmation test, 5 submaximal efforts, and 4 supramaximal running bouts at 115% of "V" ̇"O" _"2max" intensity (the first two supramaximal sessions were applied as familiarization trials) to measure the anaerobic capacity using two procedures; the maximum accumulated oxygen deficit (MAOD) and non-oxidative pathways energetics sum (AC[La-]+EPOCfast). The investigation was conducted in a single-blind and placebo-controlled manner, with participants performing the efforts first after being supplemented with a placebo (dextrose 20 g·day-1 for 5 days), and then, after a 7-day “placebo” washout period, they started the same procedure under creatine supplementation (20 g·day-1 for 5 days. This order was chosen due to the prolonged washout of creatine. MAOD was not different between placebo (3.35±0.65 L) and creatine conditions (3.39±0.79 L) (P=0.58) and presented a negligible effect [effect size (ES)=0.08], similar to, AC[La-]+EPOCfast (placebo condition=(3.66±0.79 Land under creatine ingestion =3.82 ± 0.85 L)(P=0.07) presenting a small effect (ES=0.20). The energetics from the phosphagen pathway increased significantly after creatine supplementation (1.66 ± 0.40 L) compared to the placebo condition (1.55±0.42 L) (P=0.03). However, the glycolytic and oxidative pathways were not different between conditions. Furthermore, time to exhaustion did not differ between placebo (160.79 ± 37.76 s) and creatine conditions (163.64 ± 38.72) (P= 0.49). Therefore, we can conclude that creatine supplementation improves the phosphagen energy contribution, but with no statistical effect on anaerobic capacity or time to exhaustion in supramaximal running.